Brand Image, Brand Trust, and Brand Ambassador on Purchase Decisions of Shopee E-Commerce Users in Pekanbaru City - Natasiah, Umi; Syaefulloh (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study addresses the pressing need to understand the dynamics influencing purchase decisions among Shopee users in Pekanbaru City. With the exponential growth of e-commerce platforms, such as Shopee, understanding the factors that drive consumer behavior is crucial for businesses to develop effective marketing strategies. By examining the impact of brand image, brand trust, and brand ambassador on purchase decisions, this research provides valuable insights for businesses operating in the e-commerce sector. The findings can inform marketing initiatives aimed at enhancing brand perception and fostering customer loyalty, thereby contributing to the sustainable growth of e-commerce businesses in Pekanbaru City. The study involves a sample of 150 respondents consisting of Shopee e-commerce users in Pekanbaru City, providing a comprehensive understanding of the factors influencing their purchase decisions.